Estimation of the knee joint load in sport-specific movements using wearable sensors - Stetter, B. J.; Krafft, F.; Ringhof, S.; Gruber, R.; Sell, S.; Stein, T. (Sportinformatik XII. 12. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie" vom 5.-7. September 2018 in Garching. Abstracts., 2018)
Overuse injuries of the lower limbs, such as knee pain, are common in many dynamic team sports and represent a significant problem in terms of days lost in competition (Darkos et al., 2010; Scott, et al., 2013). An imbalance between biomechanical loads and the bodies loadbearing capacities is a major risk factor for injury (Soligard et al., 2016). Conventional methods to quantify biomechanical loads, such as joint forces, are limited to a laboratory environment and involve extensive measurement equipment (i.e. motion capture system and force plates) and biomechanical modelling. In order to overcome these limitations, more and more frequently wearable sensors, such as accelerometers, are applied to measure and monitorsport-specific movements under field-based conditions. The purpose of this study was to develop a prediction model based on biomechanical reference data, which estimates the knee joint load for sport-specific movements using wearable sensor signals.